2008
DOI: 10.1529/biophysj.107.128611
|View full text |Cite
|
Sign up to set email alerts
|

Two Characteristic Regimes in Frequency-Dependent Dynamic Reorientation of Fibroblasts on Cyclically Stretched Substrates

Abstract: Cells adherent on a cyclically stretched substrate with a periodically varying uniaxial strain are known to dynamically reorient nearly perpendicular to the strain direction. We investigate the dynamic reorientation of rat embryonic and human fibroblast cells over a range of stretching frequency from 0.0001 to 20 s(-1) and strain amplitude from 1% to 15%. We report quantitative measurements that show that the mean cell orientation changes exponentially with a frequency-dependent characteristic time from 1 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
319
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(366 citation statements)
references
References 46 publications
44
319
1
2
Order By: Relevance
“…Effect of strain amplitude The studies of Kaunas et al (2005) and Jungbauer et al (2008) have demonstrated that the propensity of stress-fibers to align perpendicular to the loading direction increases with increasing applied strain-rate for a triangular imposed strain waveform. For example, as seen above with a strain amplitude of 0.1, the stress-fibers align perpendicular to the imposed loading direction when the cyclic frequency = 1 Hz but the stress-fiber distribution is approximately isotropic when = 0.1 Hz.…”
Section: 2mentioning
confidence: 99%
“…Effect of strain amplitude The studies of Kaunas et al (2005) and Jungbauer et al (2008) have demonstrated that the propensity of stress-fibers to align perpendicular to the loading direction increases with increasing applied strain-rate for a triangular imposed strain waveform. For example, as seen above with a strain amplitude of 0.1, the stress-fibers align perpendicular to the imposed loading direction when the cyclic frequency = 1 Hz but the stress-fiber distribution is approximately isotropic when = 0.1 Hz.…”
Section: 2mentioning
confidence: 99%
“…Cells are known to respond to mechanical forces exerted through surrounding fluid, adhering beads or substrates [9,[12][13][14], and they could detach, slip or roll on a substrate in response to these forces [15][16][17][18][19][20][21][22]. For example, cells on a cyclically stretched substrate tend to reorient themselves away from the stretching direction [23][24][25][26][27], and cells migrate along a substrate with rigidity gradient (durotaxis) [18]. Blood cells are found to undergo a transition from rolling to translational motion on a blood vessel wall under increasing hydrodynamic shear forces [19], exemplifying a general fact that it takes less effort for a round object to roll than to slip on a substrate [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of mechanical stimuli have the potential to regulate cellular physiology. With respect to cyclic stretch, changing the magnitude or frequency rearranges cell orientation [8,18] and cytoskeletal networks [19], and upor down-regulates cell growth rate and protein synthesis [20]. Moreover, application of a large number (~1000) of cyclic stretches also affects cell growth [21] and cell orientation.…”
Section: Resultsmentioning
confidence: 99%